2003
DOI: 10.1002/cncr.11730
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of temozolomide in patients with unresectable or metastatic soft tissue sarcoma

Abstract: BACKGROUND The objective of this study was to assess the efficacy and toxicity of the imidazotetrazine derivative temozolomide for patients with unresectable or metastatic soft tissue sarcoma. METHODS Twenty‐five of 26 patients were eligible and assessable for toxicity and response. Temozolomide was administered twice daily on a 12‐hour schedule for 5 days as an oral bolus dose of 200 mg/m2 followed by 9 doses of 90 mg/m2 every 4 weeks. RESULTS There were 2 partial responses, 2 mixed responses, and 3 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 16 publications
0
51
0
4
Order By: Relevance
“…Published studies on single-agent treatments, such as high-dose ifosfamide or temozolamide, reported a limited efficacy (17,18). Trabectedin, which has been approved in Europe for second-or further-line treatment of advanced STS, achieved response rates of ≤10%, with significant clinical benefit almost exclusively in LMS and liposarcoma patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…Published studies on single-agent treatments, such as high-dose ifosfamide or temozolamide, reported a limited efficacy (17,18). Trabectedin, which has been approved in Europe for second-or further-line treatment of advanced STS, achieved response rates of ≤10%, with significant clinical benefit almost exclusively in LMS and liposarcoma patients (19).…”
Section: Discussionmentioning
confidence: 99%
“…This therapeutic benefit was associated with silencing of the O6-methylguanine-DNA methyltransferase (MGMT) expression as determined by immunohistochemistry. All the above mentioned studies revealed good tolerance to TMZ (6)(7)(8)(9)(10)(11). The MGMT gene has been shown to be epigenetically downregulated in several solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The trial involving patients with soft tissue sarcomas not subjected to standard chemotherapy revealed only minimal efficacy of TMZ (7). Another trial on TMZ demonstrated a modest activity against previously treated unresectable or metastatic soft tissue sarcomas (8). Notably, all responding patients had leiomyosarcoma (of uterine or non-uterine origin) (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its similar mechanism of action to dacarbazine, temozolomide has been evaluated in soft tissue sarcoma using a variety of dosing schedules. In several studies which included a variety of STS subtypes, all of the clinical benefit was seen in patients with leiomyosarcoma [12][13][14].…”
Section: Introductionmentioning
confidence: 99%